"Being on both sides: covert ethnography and partisanship with bouncers in the night‐time economy". Issue 1 (14th December 2020) - Calvey, David
Abstract : Purpose: This study aims to critically expose and explore "taking sides" in the context of a covert ethnography of bouncers in the night-time economy of Manchester, UK. Design/methodology/approach: The methodology adopted is covert ethnography. The author reflects on the application and use of situated deception within an embedded and insider ethnography of bouncers, alongside other relevant covert ethnographies. Fieldwork vignettes are drawn upon to articulate the management of situated ethics and moral dilemmas. Findings: The findings argue that bouncers are a deeply maligned occupational group, who perform a valuable regulatory role in the night-time economy. Moreover, a covert role ethnographic presents an interesting liminal stance of being on both sides, rather than a reductionist choosing of a single sides. Theoretically, phenomenological bracketing and ethnomethodological indifference are used to justify the position taken in the paper. Research limitations/implications: Covert research has limitations around fieldwork time consumption, instigation tactics and "going native" distortion, alongside common fears of ethical belligerence and cavalier morals. Practical implications: The lessons learnt, particularly for early career researchers, are about pursuing creative ethnographic methods. Social implications: Occupationally, bouncers should be less demonized and more accessible to more women. This rather hyper-masculine domain should be disrupted and democratized. Originality/value: The field is relatively niche, with a purist covert ethnographic approach being an innovative way to unpack it.